Identification of the Establishment of the Regional Public Service Agency (BLUD) of Pasar Besar Ngawi in Ngawi District, Ngawi Regency - Ita Mardiani Zain,; Rindawati,; Wiwik Sri Utami,; Sri Murtini,; Bambang Sigit Widodo, (Technium Social Sciences Journal, 2023)
Improving services to merchants in traditional markets is one solution where competition and the number of modern stores are growing. The application of BLUD in traditional market management is a creation in overcoming competition. With the BLUD system, it will make the relevant regional apparatus work unit (SKPD) more flexible in managing the market, both traders and the budget generated from the merchant levy for market progress. Representative data is needed to determine the feasibility of establishing the Ngawi Large Market Market BLUD in Ngawi District, Ngawi Regency. The purpose of this study is the identification of the fulfillment of substantive, technical and administrative requirements in the establishment of BLUD in Pasar Besar Ngawi in Ngawi District, Ngawi Regency. This type of research is descriptive research using a quantitative approach. Data collection was carried out using multiple sources of evidence, namely questionnaires, interviews, documentation and direct observation. Data analysis techniques use quantitative descriptives with substantive, technical, and administrative criteria. The results of the study found that the Ngawi Large Market in Ngawi District, Ngawi Regency has not met the two criteria of substantive requirements, has met the criteria of technical requirements, and has not met the eight criteria of administrative requirements.